Zonificación de la amenaza por avenidas torrenciales en el distrito de Riohacha (LA GUAJIRA) utilizando herramientas SIG - Abello Martinez, Maria del Rosario (Universidad Antonio Nariño, 2022)
Torrential floods, described as natural problems or phenomena, result in the destruction of spaces due to the rapid and large volume transport of debris and/or sediments. For this reason, a set of different events are generated in spaces or areas, mainly in rivers and streams, perceiving that it is a problem that needs to be recognized at the national level, since it presents great disaster risks. This type of event has a destructive capacity at a social, economic, and human level, due to its different events such as debris floods or floods. The study was carried out in the District of Riohacha, with the objective of proposing a zoning of threats due to torrential floods considering a GIS tool, in this study detailed information will be obtained at a scale of 1:25000. The research has 4 phases or stages. In the first phase, the variables for the zoning of torrential hazards found in the district were identified. In the second stage, a spatial analysis of the information obtained through the variables was carried out, considering that this should be done at a scale of 1:25000. In the third, the thematic maps were generated with the GIS tool that allowed visualizing the data and the very high, high, medium, low, and very low risks of the area where the study was carried out, and in the fourth, the zoning of torrential floods and the conclusions obtained from the research for the presentation of this natural phenomenon were made.